PENGEMBANGAN BAHAN AJAR TEKS CERITA RAKYAT INDRAMAYU BERBASIS KEARIFAN LOKAL DAN PEMANFAATANNYA SEBAGAI BAHAN AJAR SMA/SMK - Fithry Muthmainnah; Unes (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to compile teaching materials for Folklore Texts in Senior High Schools/Vocational High Schools. Researchers studied folklore texts in Indramayu Regency based on structure, linguistic elements and values, to be used as Indonesian language teaching materials. This study uses a mixed method research method, namely a research method that combines or combines quantitative and qualitative methods to be used together in a research activity so that more comprehensive, valid, reliable and objective data are obtained. In this study, the first stage collects and analyzes qualitative data in answering the first and second problem formulations, namely how folklore exists in Indramayu society and its development as teaching materials for folklore texts. Then the second stage, collects and analyzes quantitative data to answer the third problem formulation, namely, how effective is the application of teaching materials for folklore texts. The data collected through this study were qualitative, describing the structure, elements, and values ​​of folklore texts in Indramayu Regency. A comprehensive review of the assessment results by two validators indicated that the five aspects fell within the range of X > 81 (validator 1) and X > 87.04 (validator 2). Therefore, the textbook